Comparison of oncological outcomes for open and laparoscopic radical nephroureterectomy: results from the Canadian Upper Tract Collaboration. (13th November 2012) - Fairey, Adrian S.; Kassouf, Wassim; Estey, Eric; Tanguay, Simon; Rendon, Ricardo; Bell, David; Izawa, Jonathan; Chin, Joseph; Kapoor, Anil; Matsumoto, Edward; Black, Peter; So, Alan; et al.
Abstract : What's known on the subject? and What does the study add?: Open radical nephroureterectomy (ORNU) with excision of the ipsilateral bladder cuff is a standard treatment for upper tract urothelial carcinoma (UTUC). However, over the past decade laparoscopic RNU (LRNU) has emerged as a minimally invasive surgical alternative. Data comparing the oncological efficacy of ORNU and LRNU have reported mixed results and the equivalence of these surgical techniques have not yet been established. We found that surgical approach was not independently associated with overall or disease‐specific survival; however, there was a trend toward an independent association between LRNU and poorer recurrence‐free survival (RFS). To our knowledge, this is the first large, multi‐institutional analysis to show a trend toward inferior RFS in patients with UTUC treated with LRNU. Objective: To examine the association between surgical approach for radical nephroureterectomy (RNU) and clinical outcomes in a large, multi‐institutional cohort, as there are limited data comparing the oncological efficacy of open RNU (ORNU) and laparoscopic RNU (LRNU) for upper urinary tract urothelial carcinoma (UTUC). Patients and Methods: Institutional RNU databases containing detailed information on patients with UTUC treated between 1994 and 2009 were obtained from 10 academic centres in Canada. Data were collected on 1029 patients and combined into a relational database formatted with patient characteristics, pathological characteristics, and survival status. Surgical approach was classified as ORNU ( n = 403) or LRNU ( n = 446). The clinical outcomes were overall survival (OS), disease‐specific survival (DSS), and recurrence‐free survival (RFS). The Kaplan–Meier method and Cox proportional regression analysis were used to analyse survival data. Results: Data were evaluable for 849 of 1029 (82.5%) patients. The median (interquartile range) follow‐up duration was 2.2 (0.6–5.0) years. The predicted 5‐year OS (67% vs 68%, log‐rank P = 0.19) and DSS (73% vs 76%, log‐rank P = 0.32) rates did not differ between the ORNU and LRNU groups; however, there was a trend toward an improved predicted 5‐year RFS rate in the ORNU group (43% vs 33%, log‐rank P = 0.06). Multivariable Cox proportional regression analysis showed that surgical approach was not significantly associated with OS (hazard ratio [HR] 0.89, 95% confidence interval [CI] 0.63–1.27, P = 0.52) or DSS (HR 0.90, 95% CI 0.60–1.37, P = 0.64); however, there was a trend toward an independent association between surgical approach and RFS (HR 1.24, 95% CI 0.98–1.57, P = 0.08). Conclusion: Surgical approach was not independently associated with OS or DSS but there was a trend toward an independent association between LRNU and poorer RFS. Further prospective evaluation is needed.